Diagnosis and Current Management of Hepatocellular Carcinoma - Satria, Rivo Armanda; Saptino Miro (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Hepatocellular carcinoma (HCC) is a primary malignant liver tumor originating from hepatocytes which has a very poor prognosis and is ranked the sixth most common cancer disease in the world and is ranked third in deaths caused by cancer worldwide. Symptoms of underlying liver diseases such as hepatitis and cirrhosis often disguise the diagnosis of HCC so that most cases are discovered at an advanced stage. The examination modalities commonly used in surveillance are liver ultrasound (USG) examination and measurement of alpha levels fetoprotein (AFP) with sensitivity diagnostic up to 90%. Non-invasive imaging plays an important role in objective recognition and staging enforcement diagnosis as early as possible so that the patient's prognosis is better. Treatment for early-stage HCC can be given through curative therapy such as resection, liver transplantation, and local ablation, but disease at an advanced stage causes limited options in management where governance The current focus is on systemic therapy with a focus on a combination strategy of immunotherapy or a combination of targeted therapy with immunotherapy as the first line.